Strategi Pembentukan Karakter Santri Melalui Program Tarbiyah di Pondok Pesantren Jannatul Qur’an Boyolali - Ibnu Abid; Mahasri Shobahiya (Kamaya: Jurnal Ilmu Agama, 2026)
This study is grounded in the need to present a model of character education that goes beyond conceptual value transmission and is realized through consistent daily habituation. The tarbiyah program at Pondok Pesantren Jannatul Qur’an Boyolali integrates character formation into the students’ twenty-four-hour daily activities. This research aims to describe the strategies of character formation implemented through the program and to identify the character values that emerge within the boarding school environment. The study employs a field research design with a descriptive qualitative approach, using participatory, interviews with the mudir, teachers, and student administrators, as well as documentation of daily activities. The findings reveal that character formation is carried out through four main strategies: teacher role modeling, the cultivation of proper conduct in daily interactions, the involvement of students in responsibility and independence, and the habituation of worship and spiritual discipline as foundational elements. These strategies are embedded in the collective life pattern of the boarding school, enabling character values to be internalized through repeated lived experiences rather than mere verbal instruction. The impact is reflected in the development of integrity, discipline, social empathy, courtesy, independence, trustworthiness, religiosity, and self-control among students. The effectiveness of the program is supported by consistent teacher exemplarity and a well-structured boarding school environment, although challenges arise from students’ diverse backgrounds and the tendency toward formal compliance without deep value internalization. Overall, the tarbiyah program represents a holistic, contextual, and practical model of character education.